Analysis of Customer Loyalty through Total Quality Service, Customer Relationship Management and Customer Satisfaction - Binsar Kristian P., Feliks Anggia; Panjaitan, Hotman (Institute of Advanced Engineering and Science, 2014)
This research talks about total quality service and customer relationship management effects toward customer satisfaction and its impact on customer loyalty.Fast Food Restaurant KFC, always strive to continue to make improvement in total quality service, so that customer satisfaction can be maintained, which in turn will have an impact on customer satisfaction increase in customer loyalty. Being able to create customer loyalty is also necessary to have a good relationship, between the customer with the restaurant.The research population was all KFC fast food restaurant customers at Rungkut Surabaya, Indonesia. From the results of the testing of the model in this research, by using accidental sampling, analysis of structural equation models, and using Amos 20 software support, the 200 respondents, was able to explain the relationship between the total service quality, customer relationship management, customer satisfaction, and customer loyalty KFC fast food restaurants Rungkut Surabaya Indonesia.The result shows that: total quality service have significant effect on customer satisfaction; total quality service have significant effect on customer loyalty; customer relationship management have significant effect on customer satisfaction; customer relationship management have significant effect on customer loyalty; customer satisfaction significantly effect customer loyalty.DOI: http://dx.doi.org/10.11591/ijere.v3i3.6191